2012
DOI: 10.1212/wnl.0b013e31826e9af8
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in albuminuria, kidney function, and risk of stroke

Abstract: Background:The objective of this study was to examine the joint associations of estimated glo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
4
25
1
1
Order By: Relevance
“…18 Similarly, we previously showed that the risk of incident stroke associated with any given strata of urinary ACR above the normal range was significantly higher in blacks than in whites even after accounting for traditional cardiovascular risk factors and eGFR. 6 The results of the current study extend these findings by showing that higher urinary ACR confers a 2-fold higher relative risk of incident CHD in blacks compared to whites with an ACR ≥30mg/g. While the absolute risk differences in the two highest categories of ACR were relatively small (~4 and 7 extra events per 1,000 person years of follow-up in blacks vs. whites, respectively), given the link between elevated urinary ACR and systemic microvascular injury, 1922 these data suggest that blacks have greater susceptibility to vascular disease than whites, which in turn may account for much of their excess risk of cardiovascular disease events such as stroke and CHD.…”
Section: Commentsupporting
confidence: 81%
See 2 more Smart Citations
“…18 Similarly, we previously showed that the risk of incident stroke associated with any given strata of urinary ACR above the normal range was significantly higher in blacks than in whites even after accounting for traditional cardiovascular risk factors and eGFR. 6 The results of the current study extend these findings by showing that higher urinary ACR confers a 2-fold higher relative risk of incident CHD in blacks compared to whites with an ACR ≥30mg/g. While the absolute risk differences in the two highest categories of ACR were relatively small (~4 and 7 extra events per 1,000 person years of follow-up in blacks vs. whites, respectively), given the link between elevated urinary ACR and systemic microvascular injury, 1922 these data suggest that blacks have greater susceptibility to vascular disease than whites, which in turn may account for much of their excess risk of cardiovascular disease events such as stroke and CHD.…”
Section: Commentsupporting
confidence: 81%
“…1 Black individuals have higher levels of urinary albumin excretion than white individuals, 26 which may contribute to racial disparities in cardiovascular outcomes. In support of this, in participants of the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study free of stroke at baseline, we previously showed that the association of urinary ACR with incident stroke differed by race, such that higher urinary ACR was independently associated with a higher risk of incident stroke in blacks but not in whites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population studies have shown that modest increases in urine albumin excretion well within the normal range of <30 mg are still relevant as they are predictive of higher mortality and ESRD risk [3941]. It is unclear if the source of the MCP-1 is interstitial versus glomerular, since increased glomerular leak of albumin or decreased tubular reabsorption could both results in increased urinary albumin excretion.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced estimated glomerular fi ltration rate (eGFR) has also been associated with a higher risk for fatal and nonfatal stroke, but the aggregate literature is not consistent [ 94 , 95 ] and there are limited data on measures of kidney function and stroke risk in blacks. In an examination of the association of eGFR and urinary albumin excretion (measured as albumin-to-creatinine ratio, ACR) with incident stroke in REGARDS, a higher ACR was found to be independently associated with higher stroke risk in black, but not white participants [ 95 ]. An editorial accompanying the paper suggests that albuminuria could be an important new marker for uncontrolled hypertension in blacks, reemphasizing the need for diagnosis of the underlying pathophysiology of the hypertension and an individualized approach to managing BP levels to reduce stroke risk in blacks [ 54 ].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%